Néantisation et lutte contre l’oubli : La représentation de la violence des conflits armés colombiens dans deux œuvres photographiques d’Erika Diettes, Río abajo (2008) et Sudarios (2011) - Emmanuelle Sinardet (Les Cahiers ALHIM)
The photographic works Río abajo (Drifting away, 2008) and Sudarios (Shrouds, 2011) by the Colombian artist Erika Diettes depict the violence of the armed conflicts of the last five decades in Colombia, through the nil produced by the enforced disappearance: the physical nothingness of the missing person, any trace of whom was erased, and the void of the crimes and their victims, left in oblivion. In a constant tension between absence and presence, the exhibitions show the emptiness left by the missing persons and the infinite suffering of their families, who are incapable to begin their process of mourning ; but they also return to them the elusive corpse in a symbolic way, by shaping a metonymical trace of the missing body. The art becomes a dignifying moral reparation, since it allows metaphoric funeral rites and the process of mourning. Furthermore, the exhibitions in sacred spaces such as temples and churches transcend the trace and transform it into a relic which, in a Christlike way, makes the missing person present. This immanent presence challenges the supreme violence of oblivion. Erika Diettes creates aura-pictures which build, protect and pass on a Colombian memory of the enforced disappearance